Effect of massage stimulation on weight gain in full term infants - Nyoman Nursari Dewi; Soetjiningsih Soetjiningsih; Endy Paryanto Prawirohartono (Indonesian Pediatric Society, 2011)
Background Massage is a tactile/kinesthetic stimulation with biochemical and physiological effects on the body. Newborn infant massage stimulation given by mothers may promote maternal-infant bonding and attachment, enhance infant weight gain and stimulate the production of breast milk. There have been few studies on the effect of massage stimulation on weight gain in full term infants, and this topic remains controversial.Objective To examine the effect of massage stimulation on weight gain in full term infants.Methods This quasi-experimental study was held in Sanglah Hospital and Bunda Setia Maternity Clinic. Massage stimulation was performed by mothers once daily for a four week period. Massage stimulation was given to 30 full term infants and their weight gain was compared to 31 control infants who did not receive massages.Results There were no differences in subject characteristics between the massage and control groups. Median weight gain in the massage group was 1230 grams, while that in the control group was 830 grams (P=0.028).Conclusion Weight gain in full term infants in the massage group was significantly greater than that in the control group after 4 weeks.